Effect of Apolipoprotein E genotype and saturated fat intake on plasma lipids and myocardial infarction in the Central Valley of Costa Rica - Yang, Yadong (2007)
We assessed the effect of APOE polymorphisms−491 A/T, C112R (APOE*4), and R158C (APOE*2) and saturated fat intake on plasma lipid levels and risk of myocardial infarction (MI) in 1,927 case subjects and 1,927 population-based control subjects matched for age, sex, and residence, all living in the Central Valley of Costa Rica. A significant gene-diet interaction ( p = 0.0157) was observed. High saturated fat intake was associated with a 49% increased risk of MI (OR = 1.49; 95% CI, 1.16–1.92) among wildtype subjects. In contrast, high saturated fat intake was associated with a 2.2- fold increased risk of MI among carriers of APOE*2 (OR = 3.17; 95% CI, 1.58–6.36) and with a 1.6-fold increase among carriers of the −491T and APOE*4 variants together (OR = 2.59; 95% CI, 1.38–4.87). Consistently, a high fat diet elicited a greater response in LDL cholesterol among carriers of APOE*2 (+17%) and APOE*4 (+14%) compared to noncarriers (+6%). The frequency of APOE variants was similar in case and control subjects, although APOE*4 homozygotes were at increased risk of MI compared to noncarriers (OR = 2.26; 95% CI, 1.03–4.98). This study supports the hypothesis that the APOE*2 and APOE*4 variants increase susceptibility to MI in the presence of high saturated fat and could explain inconsistent findings on the effects of these variants on MI in various populations.